2017
DOI: 10.3928/01477447-20161116-01
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Long Cephalomedullary Nails for Pertrochanteric Hip Fracture

Abstract: This study compared patients who underwent treatment with short or long cephalomedullary nails with integrated cephalocervical screws and linear compression. Patients with AO/OTA 31-A2 or A3 pertrochanteric fractures treated with either short (n=72) or long (n=97) InterTAN (Smith & Nephew, Memphis, Tennessee) cephalomedullary nails were reviewed. Information on perioperative measures (estimated blood loss, surgical time, and fluoroscopy time) and postoperative orthopedic complications (infection, implant failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 40 publications
(48 reference statements)
5
29
1
Order By: Relevance
“…Recent studies did not report a difference in function between patients with pertrochanteric fractures treated with either a short or a long intramedullary hip nail [ 4 , 20 ]. Similarly, other studies [ 5 , 11 ] reported similar function, fracture healing and revision rates with a short or a long intramedullary hip nail, and a shorter operative time with a short hip nail.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies did not report a difference in function between patients with pertrochanteric fractures treated with either a short or a long intramedullary hip nail [ 4 , 20 ]. Similarly, other studies [ 5 , 11 ] reported similar function, fracture healing and revision rates with a short or a long intramedullary hip nail, and a shorter operative time with a short hip nail.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies [ 5 , 11 ] reported similar function, fracture healing and revision rates with a short or a long intramedullary hip nail, and a shorter operative time with a short hip nail. Additionally, these studies emphasize on a higher rate of complications with short versus long intramedullary hip nailing [ 4 , 5 , 11 , 20 ]. An overall rate of periprosthetic femoral fractures ranging from 0 to 20% has been reported in patients treated with short intramedullary hip nails for pertrochanteric fractures [ 4 ]; some authors believe that long intramedullary nails protect the entire femur from periprosthetic fractures [ 4 ] while others report no difference in complications [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations